Gasoline Production from Coconut Oil Using The Ni-MCM-41 and Co/Ni-MCM-41 Catalyst - Lailatul Badriyah; Iip Izul Falah (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2017)
Gasoline have been produced from coconut oil using MCM-41, NiMCM-41, and Co/NiMCM-41 catalyst. The acidity of catalyst was analysed by Fourier Transformation Infra-Red Spectroscopy (FTIR). The yields of cracking product were analysed by Gas Chromatography-Mass Spectroscopy (GC-MS). The catalyst of Co/NiMCM-41 has the highest acidity than MCM-41 and NiMCM-41. It is caused by the effect of adding d orbital from Co and Ni. This cracking process is batch system, and the catalyst pellets were made at the temperature of 400 ºC. The highest gasoline product was obtained using the Co/NiMCM-41 catalyst with 89.53 % w/w yield. The major liquid product from the cracking process using MCM-41, NiMCM-41, dan Co/NiMCM-41 catalysts were estimated as 1-octena, octane, nonane; 1-octene, 1-nonene, nonane; 1-octene, octane, nonane, respectively.